2020
DOI: 10.1101/2020.07.31.231399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of a type IV CRISPR-Cas effector complex

Abstract: We reveal the structure of a type IV-B CRISPR effector (Csf) complex at 3.9 ã resolution using cryo-electron microscopy. The complex resembles the type III-A CRISPR Csm effector complex, but lacks subunits for RNA processing and target DNA cleavage, and is surprisingly assembled upon heterogeneous non-CRISPR RNA. These findings provide the first glimpse into the assembly and function of enigmatic type IV CRISPR systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Moreover, in contrast to the Csm complex, one of the catalytic residues (Asp42) of the Cas7 subtype IV-B complex is in a noncompatible position for target RNA cleavage. The study reported by Zhou et al reveals that type IV systems evolved from ancestors of type III-like systems [ 25 ].…”
Section: The Crispr–cas Systemmentioning
confidence: 99%
“…Moreover, in contrast to the Csm complex, one of the catalytic residues (Asp42) of the Cas7 subtype IV-B complex is in a noncompatible position for target RNA cleavage. The study reported by Zhou et al reveals that type IV systems evolved from ancestors of type III-like systems [ 25 ].…”
Section: The Crispr–cas Systemmentioning
confidence: 99%